Introduction to genomics - Lesk, Arthur M (OUP, 2009)
Introduction to Genomics is a fascinating insight into what can be revealed from the study of genomes: how organisms differ or match; how different organisms evolved; how the genome is constructed and how it operates; and what our understanding of genomics means in terms of our future health and wellbeing. Covering the latest techniques that enable us to study the genome in ever-increasing detail, the book explores what the genome tells us about life at the level of the molecule, the cell, the organism, the ecosystem and the biosphere. Learning features throughout make this book the ideal teaching and learning tool: extensive end of chapter exercises